Collaborative and individual writing in a classroom: an analysis of texts written by students of fundamental teaching - Felipeto, Sonia Cristina Simões (2019)
Collaborative writing for classroom dyads is a didactic situation that places students dialoguing to build a single text through negotiation, unlike individual writing, where one usually writes alone and in silence. Affiliated to the studies proposed by Textual Genetics based on an enunciative approach, the objective of this work was to develop a comparative study with the purpose of highlighting the advantages and / or disadvantages of writing in collaboration. Three categories served as analytical parameters: A - textual extension, measured by the number of words ; B - the incidence of orthographic errors; C) the number of erasures. The study sample was defined by convenience and comprises 8 manuscripts, 4 of which are individually produced and 4 are produced in pairs. The students are in the 2nd year of elementary school in Brazil, with ages between 7 and 8 years. The data were collected respecting the ecological conditions of the school context. Analyzes have shown that, collaboratively, students write, on average, texts 34% longer than individually, produced 170% more erasures and 10% more errors than in the individual format.